Moisture dependent thermal properties of selected vegetables in Akwa Ibom State, Nigeria - Olugbenga Abiola Fakayode; Olayemi Olubunmi Ojoawo (Research in Agricultural Engineering, 2019)
The thermal properties of some selected vegetables in Akwa Ibom State, Nigeria were investigated. The specific heat, thermal conductivity and thermal diffusivity for the five selected vegetables (Afang, Nkong, Atama, Editan and Nton) were determined and the moisture content variation was investigated. The specific heat values ranged from 2,348-4,580 J.kg-1.K-1, while the thermal conductivity values ranged from 0.00368-0.489 and the thermal diffusivity values ranged from 1.03 × 10-7-1.99 × 10-7 m2.s-1. Nton had the highest specific heat and thermal conductivity, while Editan had the highest diffusivity. An increase in the moisture content increased the specific heat, thermal conductivity and diffusivity of the vegetables and the relationships were found to be linear. Regression equations for the thermal properties were established as a function of the product's moisture content with the experimental data from this study. The thermal properties of the vegetables varied linearly with the moisture content and there were significant differences in the thermal properties of the selected vegetables.